2023
DOI: 10.1186/s13018-023-03929-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single- and double-dose intravenous tranexamic acid in hip and knee arthroplasty: a systematic review and meta-analysis

Abstract: Objective With the increasing prevalence of osteoarthritis of the hip and knee, total joint replacement, the end-stage treatment, provides pain relief and restoration of function, but is often associated with massive blood loss. Tranexamic acid (TXA) has been reported to reduce perioperative blood loss in hip or knee arthroplasty. However, the optimal dose of TXA administration remains controversial. Therefore, we performed a meta-analysis combining data from 5 trials comparing the efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Tranexamic acid, a synthetic plasmin inhibitor, can inhibit fibrin degradation and promote coagulation by competing for the binding sites of plasminogen and plasminogen lysine. 47 It has been widely recognized by orthopedic surgeons 12 , 48 , 49 because it effectively reduces intraoperative blood loss, 50 lowers the risk of blood transfusion, and does not increase the probability of deep venous thrombosis (DVT). 51 , 52 In our study, the intraoperative use of tranexamic acid was identified as an independent risk factor for postoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid, a synthetic plasmin inhibitor, can inhibit fibrin degradation and promote coagulation by competing for the binding sites of plasminogen and plasminogen lysine. 47 It has been widely recognized by orthopedic surgeons 12 , 48 , 49 because it effectively reduces intraoperative blood loss, 50 lowers the risk of blood transfusion, and does not increase the probability of deep venous thrombosis (DVT). 51 , 52 In our study, the intraoperative use of tranexamic acid was identified as an independent risk factor for postoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid (TXA) is a well-established antifibrinolytic agent that has been shown to reduce blood loss during joint replacement, cardiac surgery, and spine surgery (1)(2)(3). In spine surgery, perioperative bleeding can have serious consequences, including spinal cord injury and compression of the esophagus and trachea by hematoma (4).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological aspects of medicinal drugs including the selection and application of effective dose protocols are critical for the treatment of patients in all diseases. For example, individual variations in drug responses [1], differences among populations [2], different drug formulations [3], single or multiple drug administration [4] and different routes of drug administration [5] all have different effects on treatments. Similarly, the need for optimal, target-specific therapies including drug combinations as well as other parameters will also effect overall treatments [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%